Penentuan Waktu Solat Subuh Menggunakan Rubu' Mujayyab di Malaysia - Ahmad Zaki, Nurul Huda; Zainuddin, Mohd Zambri; Ali, Abdul Karim; Abdul Wahab, Raihana; Mohd Nawawi, Mohd Saiful Anwar; Abdul Niri, Mohammaddin; Ismail, Khadijah (Jurnal Fiqh, 2014)
Astronomical instruments have been used in Arabia to aid the process of determining the accurate times, qibla direction and several issues regarding Muslim worship since the 7th century AD. The technical instruments are used together with the knowledge of astronomy and mathematics. As a result, 'ilm al-Miqat has been introduced as a part of the Syariah discipline. Through 'ilm al-Miqat, prayer times are no longer determined by the naked eye, but are calculated with the aid of astronomical instruments.Among the popular astronomical instruments that are used in the method of 'ilm al-Miqat are the astrolabe and rubu' mujayyab. Indeed, rubu' mujayyab has also been used in Malaysia to determine prayer times. Therefore, this research aims to study the methods concerning how Subuh prayer time is calculated in Malaysia using rubu' mujayyab. The results of the comparison between the methods of calculation using rubu' mujayyab and those that use electronic devices in terms of the timing of the Subuh prayer, showed that there is a similarity in terms of the concept used in both methods of calculation. Thus, it can be concluded that the current prayer time calculation methods are generated based on the calculation concept using rubu' mujayyab.